Reduced Introgression of Sex Chromosome Markers in the Mexican Howler Monkey (Alouatta palliata × A. pigra) Hybrid Zone - Liliana Cortés-Ortiz; Marcella D. Baiz; Javier Hermida-Lagunes; Francisco García-Orduña; Ariadna Rangel-Negrín; Dawn M. Kitchen; Thore J. Bergman; Pedro A. D. Dias; Domingo Canales-Espinosa (International Journal of Primatology, 2019)
Interspecific hybridization allows the introgression or movement of alleles from one genome to another. While some genomic regions freely exchange alleles during hybridization, loci associated with reproductive isolation do not intermix. In many model organisms, the X chromosome displays limited introgression compared to autosomes owing to the presence of multiple loci associated with hybrid sterility or inviability (the “large X-effect”). Similarly, if hybrids are produced, the heterogametic sex is usually inviable or sterile, a pattern known as Haldane’s rule. We analyzed the patterns of introgression of genetic markers located in the mitochondrial (control region) and nuclear (autosomal microsatellites and sex chromosome genes) genomes of two howler monkey species ( Alouatta palliata and A. pigra ) that form a natural hybrid zone in southern Mexico, to evaluate whether the large X-effect and Haldane’s rule affect the outcomes of hybridization between these sister species. To identify the level of admixture of each individual in the hybrid zone ( N = 254) we analyzed individuals sampled outside the hybrid zone (109 A. pigra and 39 A. palliata ) to determine allele frequencies of parental species and estimated a hybrid index based on nuclear markers. We then performed a cline analysis using individuals in the hybrid zone to determine patterns of introgression for each locus. Our analyses show that although the hybrid zone is bimodal (with no known F1 s and few recent generation hybrids) and quite narrow, there has been extensive introgression in both directions, and there is a large array of admixed individuals in the hybrid zone. Mitochondrial and most autosomal markers showed bidirectional introgression, but some had biased introgression toward one species or the other. All markers on the sex chromosomes and a few autosomal markers showed highly restricted introgression. This pattern is consistent with the hypothesis that the sex chromosomes make a disproportionate contribution to reproductive isolation, and our results broaden the taxonomic representation of these patterns across animal taxa.